Wellness tourism: social-based tourism strategy in the covid-19 era in Bandung good guide - Fanji Lesmana; Elly Malilah; Rini andari (Universitas Merdeka Malang, 2022)
This research aims to analyze how Bandung Good Guide can present tourist packages/activities during the COVID-19 pandemic circumstances. This research took place in Bandung, from September to November 2021 and uses a qualitative descriptive approach, also previous academic literature studies that address wellness tourism and the social economy. During the pandemic, the government has various programs in controlling the spread of the COVID-19 virus by restricting people's movements, prohibiting people from traveling far, and closing tourist attractions, which feels like the end of the tourist travel industry. But for people who called Bandung Good Guide, initiating a new tourism business concept, they created a travel program called “everyday tour”. Where the tour runs every day with a different theme and topic every day also uses a payment system pay as you go with a minimum payment, which turned out to be in great demand and gave positive appreciation for the guides. Presenting a social vision that wants to increase the value of a professional tour guide and increase the tourist's time -stay to travel in the city of Bandung, making this business concept, not just a general business, it turns interested tourists. The results of this article turn that the COVID-19 pandemic is not the end of the tourism business. Using the concept of health tourism with a social touch in packaging products turns out that tourists are not afraid to participate in tourist programs/activities during the COVID-19 pandemic.